2016
DOI: 10.1097/ccm.0000000000001410
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Massive Transfusion

Abstract: This large-scale study based on nationwide data from Sweden and Denmark describes the complete range of massive transfusion. We report a nonnegligible incidence and both a high absolute mortality and high standardized mortality ratio. The general pattern was similar for Sweden and Denmark, and we believe that similar patterns may be found in other high-resource countries. The study provides a relevant background for clinicians and researchers for designing future studies in this field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(24 citation statements)
references
References 21 publications
(20 reference statements)
1
20
0
3
Order By: Relevance
“…Patients with UGIB require continuous monitoring, fluid therapy, and transfusion after admission, as well as complex treatments, including endoscopic, radiologic, or surgical treatment 34. In addition, apart from trauma and surgery, UGIB is one of the most common conditions requiring massive transfusion (MT) 5. A previous study showed that massive bleeding occurs in 5.7% of patients with total UGIB and was fatal in 70% of the patients with massive bleeding in this study 6…”
Section: Introductionmentioning
confidence: 60%
“…Patients with UGIB require continuous monitoring, fluid therapy, and transfusion after admission, as well as complex treatments, including endoscopic, radiologic, or surgical treatment 34. In addition, apart from trauma and surgery, UGIB is one of the most common conditions requiring massive transfusion (MT) 5. A previous study showed that massive bleeding occurs in 5.7% of patients with total UGIB and was fatal in 70% of the patients with massive bleeding in this study 6…”
Section: Introductionmentioning
confidence: 60%
“…Finally, 6 studies [ 15 , 17 19 , 21 , 23 ] were included in our meta-analysis after full-text reading. Among them, there were 2 RCTs [ 18 , 19 ] and 4 RCSs [ 15 , 17 , 21 , 23 ]. General characteristics of the included RCTs can be seen in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…However, recently, other studies have reported different conclusions [ 18 , 23 ]. In the O’Neal et al study [ 18 ], the VAS scores of IV acetaminophen and placebo groups were compared, as well as total the morphine consumption, among other parameters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations